2007
DOI: 10.1200/jco.2006.08.1463
|View full text |Cite
|
Sign up to set email alerts
|

Identification of High-Risk Patients Among Those Diagnosed With Thin Cutaneous Melanomas

Abstract: Prognostication and related clinical decision making in the majority of patients with melanoma can be improved now using the validated, SEER-based classification. Tumor cell mitotic rate should be incorporated into the next iteration of AJCC staging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
169
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(180 citation statements)
references
References 28 publications
7
169
1
3
Order By: Relevance
“…Because disease can recur even among individuals with localized lesions despite appropriate surgical procedures, identifying independent prognostic markers in addition to stage at diagnosis has been a priority. Presently, nine additional independent clinicopathologic prognostic markers for CMM have been identified [e.g., age at presentation, gender, Breslow thickness (mm), Clark level of invasion, lesion ulceration, tumor-infiltrating lymphocyte status, presence of microsatellite lesions, degree of vascular and/or lymphatic invasion, and quantity of mitotic figures] and have been used to establish clinically validated risk stratifications among melanoma patients (2,3). Yet, in CMM (4,5), as well as in other cancers (6,7), the association of differential gene expression profiles with prognosis among histologically identical lesions has prompted the desire to enhance clinicopathologically derived prognostic models with molecular markers representative of the tumor subclasses.…”
Section: Introductionmentioning
confidence: 99%
“…Because disease can recur even among individuals with localized lesions despite appropriate surgical procedures, identifying independent prognostic markers in addition to stage at diagnosis has been a priority. Presently, nine additional independent clinicopathologic prognostic markers for CMM have been identified [e.g., age at presentation, gender, Breslow thickness (mm), Clark level of invasion, lesion ulceration, tumor-infiltrating lymphocyte status, presence of microsatellite lesions, degree of vascular and/or lymphatic invasion, and quantity of mitotic figures] and have been used to establish clinically validated risk stratifications among melanoma patients (2,3). Yet, in CMM (4,5), as well as in other cancers (6,7), the association of differential gene expression profiles with prognosis among histologically identical lesions has prompted the desire to enhance clinicopathologically derived prognostic models with molecular markers representative of the tumor subclasses.…”
Section: Introductionmentioning
confidence: 99%
“…4,10 Additionally, although most thin melanomas (Breslow thickness r1 mm) have a favorable prognosis, some thin melanomas are more aggressive; consequently, there is a need to identify thin melanomas with a more aggressive potential to guide management. 4,11,12 Insulin-like growth factor-II (IGF-II) messenger RNA (mRNA)-binding protein-3 (IMP-3), also known as K homology domain-containing protein overexpressed in cancer (KOC) and L523S, is a member of the IGF-II mRNA-binding protein (IMP) family, which also includes IMP-1 and IMP-2. 13 IMP-3 is a 580 amino-acid protein encoded by a 4350-bp mRNA transcript produced by a gene located on chromosome 7p11.5.…”
mentioning
confidence: 99%
“…Barnhill et al compared the values of MR vs. ulceration in predicting the prognosis of localized melanoma; multivariate analysis of MR, ulceration, and tumor thickness showed that MR (<1, 1−6, and >6) is the most independent prognostic factor. In addition, some other studies also confirmed that MR is an important prognostic factor of skin melanoma (25)(26)(27)(28). According to the AJCC staging system (2010 edition), patients with an MR value of ≥1 is an independent prognostic factor of poor prognosis, in particular in patients with an infiltration thickness of ≤1 mm.…”
Section: Pathology Reportmentioning
confidence: 84%